Oxidative stress and hematocrit levels in eared doves (Zenaida auriculata) exposed to neonicotinoid-treated soybean cotyledons - Addy Orduna, Laura; Cazenave, Jimena (Ediciones INTA, 2025)
This study evaluates the effects of exposure to neonicotinoid-treated soybean cotyledons on oxidative stress markers and hematocrit in eared doves (Zenaida auriculata). Thirty-two doves (eight by treatment) were exposed to cotyledons from soybean treated with imidacloprid (IMI1: 0.4 mg a.i./g seed and IMI2: 1.2 mg a.i./g seed) and thiamethoxam (TMX: 0.7 mg a.i./g seed), and cotyledons from untreated soybean as a control, plus commercial seed mix (maintenance food). The concentrations of neonicotinoids used corresponded to those typically applied in soybeans as seed treatment in the field with commercial formulations. The exposure to the chemicals was intermittent, alternating weekly over a four-week period. This design simulates real-world scenarios where birds may encounter both treated and untreated fields, as well as a variety of seeds. Results indicate no significant changes in hematocrit, hepatic and cerebral glutathione S-transferase (GST), hepatic catalase (CAT), or hepatic lipid peroxidation (LPO) levels across treatments compared to the control. The neonicotinoid concentrations used in soybean seed treatments appear to be insufficient to induce oxidative damage in these birds under intermittent exposure conditions. These findings underscore the importance of studying various exposure scenarios to better understand the potential environmental risks posed by neonicotinoid-treated seeds.